2020
DOI: 10.1371/journal.pone.0229598
|View full text |Cite
|
Sign up to set email alerts
|

Risk of coronary heart disease in the rural population in Xinjiang: A nested case-control study in China

Abstract: Background and aimCoronary heart disease (CHD) is a chronic complex disease caused by a combination of factors such as lifestyle behaviors and environmental and genetic factors. We conducted this study to evaluate the risk factors affecting the development of CHD in Xinjiang, and to obtain valuable information for formulating appropriate local public health policies. MethodWe conducted a nested case-control study with 277 confirmed CHD cases and 554 matched controls. The association of the risk factors with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The incidence rate of CHD in this study was 15.15/1000 person-years for people with disabilities, while it was 16.59/1000 person-years for those with physical disabilities. This result far exceeds the 5.57–6.37/1000 person-years from cohort studies in the general Chinese population [ 25 , 26 ]. Consistent with the previous studies, our results demonstrated that people with disabilities have a higher risk of CHD than their healthy peers.…”
Section: Discussionmentioning
confidence: 72%
“…The incidence rate of CHD in this study was 15.15/1000 person-years for people with disabilities, while it was 16.59/1000 person-years for those with physical disabilities. This result far exceeds the 5.57–6.37/1000 person-years from cohort studies in the general Chinese population [ 25 , 26 ]. Consistent with the previous studies, our results demonstrated that people with disabilities have a higher risk of CHD than their healthy peers.…”
Section: Discussionmentioning
confidence: 72%
“…Traditionally, most epidemiological studies and treatment algorithms have considered the CHD risk factors as independent predictors [ 8 ], which may distort conclusions due to unidentified interactions. This is somewhat surprising as studies addressing the interactions across CHD risk factors have emphasised their importance and revealed associations of modifiable risk factors particularly with the family history and genetic risk [ 9–13 ], but also across the modifiable risk factors, for example, between dyslipidemia and smoking, dyslipidemia and hypertension, dyslipidemia and obesity, and diabetes and hypertension [ 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The growing burden of CHD has been a main public health problem in China (6). Despite the pathogeny of CHD is not entirely clear, risk factors such as age, gender, obesity, diabetes, high cholesterol, high blood pressure, and unhealthy living habits like smoking, could explain about 50-60% of the etiology of CHD (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%